Penerapan Metode MAUT Terhadap Perkembangan Metaverse Untuk Media Pembelajaran Daring Dengan Pembobotan ROC - Pristiwanto Pristiwanto; Hery Sunandar; Berto Nadeak (STMIK Budi Darma, 2022)
Decision support system is a method that helps in making decisions from a problem with semi-structured or unstructured conditions. One of them is in implementing online learning media in the current Metaverse era. Metaverse is defined as a virtual space designed to include all stakeholders, especially all supported devices, facilitating communication with regional seamless Internet connectivity. Its application in the field of education has a very high opportunity in supporting the process of developing a more advanced education implementation. However, its use will damage physical and psychological health, increase the risk of sexual harassment so that it becomes addicted and forgets time. Therefore, the role of DSS in solving this problem is urgently needed by applying the MAUT method and ROC weighting. In this study, the results of the MAUT method, the best alternative is A2 for Google Classroom with a value of 0,597.